ØªØØ¯ÙØ§Øª Ø§ÙØ¥Ø¯Ø§Ø±Ø© Ø§ÙØ¥ÙÙØªØ±ÙÙÙØ© ÙÙ Ø§ÙØ¬Ø²Ø§Ø¦Ø± Ø¯Ø±Ø§Ø³Ø© Ø³ÙØ³ÙÙÙÙØ¬ÙØ© Ø¨Ø¨ÙØ¯ÙØ© Ø§ÙÙØ§ÙÙØªÙØ³ Ø¨Ø§ÙØ¹Ø§ØµÙØ© - Ø¯Ø¨ÙØ©, Ø§ÙØ£Ø³ØªØ§Ø° Ø§ÙØ¯ÙØªÙØ± : Ø¹Ø¨Ø¯ Ø; Ø¹Ø¨Ø§Ù, Ø§ÙØ¨Ø§ØØ«: Ø¹Ø¨Ø¯ Ø§ÙÙØ§Ø¯Ø± (Sciences de l'Homme et de la SociÃ©tÃ©, 2015)
Ø§ÙØ¨ÙØ¯ÙØ© Ø¨Ø§Ø¹ØªØ¨Ø§Ø±ÙØ§ Ø§ÙØ¥Ø¯Ø§Ø±Ø© Ø§ÙØ£ÙØ±Ø¨ Ø¥ÙÙ Ø§ÙÙÙØ§Ø·Ù ÙØ§ÙÙÙØ§Ø© Ø§ÙØ±Ø¦ÙØ³Ø© ÙÙ Ø§ÙÙØ¬ØªÙØ¹ ÙÙÙ ØªØªØ´ÙÙ ÙÙ ÙÙÙÙÙ Ø®Ø¯ÙØ© Ø§ÙÙÙØ§Ø·Ù ÙÙÙÙØ§Ø·Ù ØªØØª ØªÙØ¸ÙÙ Ø¥Ø¯Ø§Ø±Ù ÙØÙÙ ÙØªØ¨Ø¹ Ø³ÙØ§Ø³Ø© Ø§ÙÙØ±ÙØ²ÙØ© Ø§ÙØ¥Ø¯Ø§Ø±ÙØ©Ø ÙÙÙ Ø£ÙØ«Ø± Ø¥Ø¯Ø§Ø±Ø© ÙÙØµØ¯ÙØ§ Ø§ÙÙÙØ§Ø·Ù ÙÙØ¶Ø§Ø¡ ÙØµØ§ÙØÙ Ø§ÙØ¥Ø¯Ø§Ø±ÙØ© ÙÙØ§ ÙØ³ØªÙØ¬Ø¨ ØªÙØ¸ÙÙ ÙÙÙÙÙØ© Ø¥Ø¯Ø§Ø±Ø© Ø§ÙØ¨ÙØ¯ÙØ© ÙÙÙ ÙØ§ ØªÙØªØ¶Ù Ø¸Ø±ÙÙ ÙÙØªØ·ÙØ¨Ø§Øª Ø§ÙÙÙØ§Ø·Ù Ø§ÙÙØÙÙ ÙÙ Ø®ÙØ§Ù Ø¥Ø¯Ø®Ø§Ù Ø§ÙØªÙÙÙÙÙØ¬ÙØ§ Ø§ÙØØ¯ÙØ«Ø© ÙØªØ·ÙÙØ±ÙØ§ ÙÙ ØªØµØ¨Ø Ø¥Ø¯Ø§Ø±Ø© Ø¥ÙÙØªØ±ÙÙÙØ©. Â  Abstract: Municipality represent the closest administration to the citizen and the nucleus major in the community, it made up of the concept of citizen service to the citizen under tight administrative organization follows the administrative central policy, and the municipality is more management destination for citizens to spend administrative interests, which requires organization and restructuring of the municipal administration as required conditions and requirements of the local citizens through the use of modern technology and develop it in order to become an electronic management.